The Role-Playing Method in English Language Learning to Reduce Speaking Anxiety Among First-Semester Students at APIKES Talitakum Medan - Lily Lily; Cut Roza Asminanda (Journal of Innovative and Creativity, 2026)
This study employed a quasi-experimental pretest-posttest design to examine the effectiveness of the role-playing method in reducing speaking anxiety among first-semester students in English speaking skills courses. The experimental class consisted of 32 first-semester students from the Radiology study program. The data analysis technique used was quantitative descriptive analysis, supported by a t-test statistical procedure. The results of the t-test showed a significance value (2-tailed) of 0.00. Since the significance value is less than 0.05, the null hypothesis (H₀) is rejected, and the alternative hypothesis (H₁) is accepted. This indicates that the implementation of the role-playing method, particularly through drama-based learning activities, is effective in reducing students' speaking anxiety in English classes